THE PROCESS OF STAGING OUR NATIONAL DANCES ON PUBLIC HOLIDAYS (Archive of Conferences, 2021)
This article was one of the forms of events public holidays, its importance in the education of people, its organization, management and problems of dances staged in it and its solution were mentioned.